DAMPAK KONTEN NEGATIF MEDIA SOSIAL TERHADAP MORALITAS REMAJA: STUDI KUALITATIF PSIKOLOGI - Siti Sazkia Ashara; Sri Yuanita Talingansing; Zahra Tusyita; Moh Noufal A. Razak; Deantri Djalil (CV. ADIBA AISHA AMIRA, 2026)
This study aimed to explore the influence of negative social media content exposure on adolescent morality from a psychological perspective. The research employed a qualitative approach using an Interpretative Phenomenological Analysis (IPA) design. Participants consisted of 20 adolescents aged 13–18 years selected through purposive sampling. Data were collected through semi-structured in-depth interviews, limited participatory observation, and digital journals. The data were analyzed using thematic analysis. The findings revealed that exposure to negative content generally occurred unintentionally through social media recommendation algorithms. Repeated exposure potentially led to desensitization toward violence, decreased empathy, normalization of aggressive behavior, and shifts in adolescents' moral values. However, family support, digital literacy, character education, and involvement in positive activities were identified as protective factors that helped adolescents maintain their moral values. This study highlights the importance of collaboration among families, schools, and communities in strengthening adolescents' moral resilience in the digital era.